Air pollution, temperature and mumps: A time-series study of independent and interaction effects - Haoyue Cao; Rongrong Xu; Xiqian Lu; Wenguo Jiang; Lihua Wang; Miao Yu; Wenjun Wang; Juxiang Yuan (Ecotoxicology and Environmental Safety)
Understanding the associations of air pollutants and temperature with the incidence of mumps, and exploring the interaction effects of heat index (HI) and air pollutants, are crucial for disease intervention under the context of climate change. This time-series study was conducted in Jining city using data on daily mumps cases, meteorological factors and air pollutants obtained from 2015 to 2021. Distributed lag models combined with quasi-Poisson regressions were applied to examine these associations. The findings indicated a heightened risk of mumps in correlation with elevated exposure to PM2.5, PM10, and NO2. Specifically, the precent changes in the risk of mumps were 0.6 % and 0.3 % associated with per 10 μg/m3 increment in PM2.5 and PM10 at lag0 day, respectively. The cumulative effects of temperature were significantly associated with mumps, showing a ''U''-shape pattern. Compared to the minimum effect value of 4 ℃, relative risk (RRs) of mumps for high and low temperature (at the 90th and 10th percentiles) were 1.961 (1.106–3.477) and 1.058 (0.976–1.158), respectively. There were significant synergistic effects between particulate matters (PMs) and HI. Compared to the low concentrations of PMs and normal heat index (NHI), co-exposure to high PMs and high heat index (HHI) has the highest risk (RRPM2.5: 1.32 and, RRPM10: 1.30). Individuals aged over 5 years was susceptible to particulate matters (PMs). Our results suggested that mitigating both PM and high temperature exposure may bring more health benefits for mumps incidence.